ADCY5 mutation carriers display pleiotropic paroxysmal day and nighttime dyskinesias - Friedman, Jennifer R.; Méneret, Aurélie; Chen, Dong-Hui; Trouillard, Oriane; Vidailhet, Marie; Raskind, Wendy H.; Roze, Emmanuel (Movement disorders, 2016)
This work was supported by a research support provided by Merz-Pharma. Dr. Roze is the recipient of a grant “poste d'accueil” AP-HP/CNRS. Dr Méneret is the recipient of a grant from JNLF. Support was also received from NIH R01NS069719 (Drs. Raskind and Chen) and the Department of Veterans Affairs (Dr. Raskind).